Faktor Kepopuleran Kajian Dr. H. Fahrudin Faiz, S.Ag., M.Ag. di Kalangan Generasi Z - Afifah, Sarah; Arwani, M. Khairul (IDRIS Darulfunun Institute, 2023)
This research investigates the factors that contribute to the appeal of Dr. Fahrudin Faiz's religious studies among Generation Z. In an era where the delivery method and popularity significantly influence religious outreach (Dakwah), this study aims to understand the dynamics of engaging young audiences. A qualitative field research method, comprising observation, interviews, and documentation, is utilized to gather data. The study seeks to offer comprehensive insights into Generation Z's motivations and preferences concerning religious teachings. The findings are anticipated to assist educators, researchers, and stakeholders in developing improved communication strategies for imparting religious values in today's digital world. This research not only highlights the intersection of religion and modern communication channels but also addresses the specific needs and interests of younger generations in religious education.